Association between training and organizational commitment - Shahzadi, Aqsa (060482) 2010 (Islamabad. Department of Business Administration (Air University Main Campus), 2010)
The study basically aims to identify and understand the relationship between training and the three different kinds of organizational commitments. The purpose of the research was to see whether training activities motivated employees to stay with the organization or not and how. Training was divided into two parts, training benefits and employee perceptions regarding training and the organizational efforts to fulfill their training needs. The effect of these two independent variables was studied on the three dependent variables affective, normative and continuance commitment. In order to find the relationship between these variables, questionnaires were used to collect the data from the two major telecommunication companies, Mobilink and Ufone operating in Islamabad. Regression and correlation were used to determine the results. The study revealed the existence of a relationship between the independent variables and the three kinds of organizational commitments. Although the two independent training variables affected organizational commitment, employee perceptions regarding trainings and the organizational efforts to fulfill their training needs, were found to have a greater impact.
BBA